Lomerizine, a Ca(2+) Channel Blocker, Protects against Neuronal Degeneration within the Visual Center of the Brain after Retinal Damage in Mice - Ito, Yasushi (CNS Neurosci Ther, 2009)
The purpose of this study was to determine whether lomerizine, a Ca(2+) channel blocker, protects against neuronal degeneration within the dorsal lateral geniculate nucleus (dLGN) and superior colliculus (SC) after the induction of retinal damage by intravitreal injection of N‐methyl‐d‐aspartate (NMDA) in mice. NMDA (20 mM/2 μL) was injected into the vitreous body of the left eye in mice (DAY 0). Lomerizine at 30 mg/kg, p.o. was administered daily from immediately after the injection of NMDA (DAY 0) to 90 days after (DAY 90). To investigate the neuroprotective effects of lomerizine, the retina, dLGN, and SC were examined using histochemistry and immunohistochemistry. Lomerizine reduced the retinal damage induced by NMDA and partially prevented the transsynaptic neuronal degeneration within dLGN and SC on the contralateral side. Moreover, lomerizine reduced the intravitreal NMDA induced decrease in the light‐induced expression of c‐Fos in the contralateral dLGN (used in this study to evaluate residual vision). These results indicate that lomerizine affords some protection against transsynaptic neuronal degeneration within the visual center of the mouse brain.